2018
DOI: 10.1002/chem.201705847
|View full text |Cite
|
Sign up to set email alerts
|

Umpolung at Boron: Ancillary‐Ligand‐Induced Formation of Boron‐Based Donor Ligands from Phosphine‐Boranes

Abstract: Easy-to-prepare η -coordinated phosphine-borane ligands are demonstrated to liberate hydrogen upon treatment with different σ-donor/π-acceptor ligands (CO, tBuNC, CN ). Depending on the utilized ancillary ligand, different reaction pathways are observed, ranging from simple hydride protonation to iron-boron bond formation and subsequent rearrangement to pincer-type ligands based on a tricoordinate boron centre. The last-named reactivity is in line with a formal umpolung at the boron centre from a Lewis acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
(136 reference statements)
0
17
0
Order By: Relevance
“…Langer reported the synthesis of a PBP–Fe complex 35 by reaction of a boronium salt with Fe(CO) 5 , which proceeded via dissociation of CO ligands and oxidative addition of the B–H bond to Fe under photoirradiation conditions (Scheme 14). 50,51 Structural analysis showed that the central boron atom of the Fe–B complex 35 can be best regarded as a borylene stabilized by bis(phosphino)methane linkers. The PBP–Fe complex 35 catalyzed a dehydrogenation reaction of dimethylamine-borane efficiently (Scheme 15).…”
Section: Catalysis Using M–e Complexes In Synthetic Reactionsmentioning
confidence: 99%
“…Langer reported the synthesis of a PBP–Fe complex 35 by reaction of a boronium salt with Fe(CO) 5 , which proceeded via dissociation of CO ligands and oxidative addition of the B–H bond to Fe under photoirradiation conditions (Scheme 14). 50,51 Structural analysis showed that the central boron atom of the Fe–B complex 35 can be best regarded as a borylene stabilized by bis(phosphino)methane linkers. The PBP–Fe complex 35 catalyzed a dehydrogenation reaction of dimethylamine-borane efficiently (Scheme 15).…”
Section: Catalysis Using M–e Complexes In Synthetic Reactionsmentioning
confidence: 99%
“…As previously noted, borylenes are not likely to be sufficiently stabilized by tertiary phosphines to allow for their isolation, but these species have been reported as ligands coordinated to a transition metal . In the case of aluminum(I), the situation is different: although the Fe−Al interaction is rather strong, the AlH fragment as a coordinated ligand is not sufficiently stabilized by tertiary phosphine substituents.…”
Section: Resultsmentioning
confidence: 97%
“…As previously noted, borylenes are not likely to be sufficiently stabilized by tertiaryp hosphines to allow for their isolation, [11] butthese specieshave been reported as ligandscoordinated to at ransition metal. [12,13,18,19] In the case of aluminum(I), the situation is different:a lthought he FeÀAl interaction is rathers trong, the AlH fragment as ac oordinated ligand is not sufficiently stabilized by tertiary phosphine substituents.H owever,w ith carbenes as stabilizing substituents, iron complexes containing ligand-stabilized aluminum(I) as ad onor ligand can be isolated. [20] Moreover,o ur findings show that, for X = BH, CH, and C, the bond in thesec omplexes can be interpreted as ad onor-acceptor bond from the phosphines to the central group, whichi tself acts as an electron-donatingl igand.…”
Section: Eda-nocv Results Of Iron Complexes 2a-dmentioning
confidence: 99%
“…The X‐ray structural analysis demonstrated the added chloride bonds to Ir, not to Ga, to form the octahedral iridium trichloride complex bearing a GaCl as a supporting ligand (Figure b). The coordination geometry of ligands on Ir except for the GaCl in 4 is square‐pyramidal, judged by the τ parameter ( τ =0.11), indicating that the GaCl is a donor ligand to the Ir . Therefore, in these complexes, the Ir can be described as an Ir III , and Ga as a neutral Ga I , gallylene, generated through two‐electron reduction of 2 by the added Ir I in terms of the formal oxidation state .…”
Section: Figurementioning
confidence: 99%